BOSHLANGʻICH SINF OʻQUVCHILARINING NUTQ MADANIYATINI RIVOJLANTIRISH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article discusses the issues of developing speech culture in primary school students. The pedagogical importance of forming oral and written speech, observing language norms, enriching vocabulary, and developing fluent and expressive communication skills is analyzed. The role of effective methods and interactive approaches used in mother tongue lessons in improving speech culture is also highlighted.